Orthoplastic Reconstruction of Type IIIB Open Tibial Shaft Fractures Using Debrided, Devitalized Cortical Segments: Health-Related Quality-of-Life Outcomes. Issue 7 (July 2022) - Al-Hourani, Khalid; Pearce, Oliver; Stoddart, Michael; Riddick, Andrew; Khan, Umraz; Kelly, Michael B.
Abstract : Objective: To determine health-related quality of life (HRQoL) in patients who sustained type IIIB open tibial diaphyseal (OTA/AO-42) fractures and underwent orthoplastic reconstruction using mechanically relevant devitalized bone (ORDB) versus those who did not require the use of devitalized bone as part of their orthoplastic reconstruction. Design: Consecutive cohort study. Patients/Participants: The study included 74 patients who sustained a type IIIB open tibial diaphyseal fracture requiring orthoplastic reconstruction over a 4-year period in a major trauma center. All patients underwent a two-stage orthoplastic reconstruction protocol, with the second stage consisting of definitive fixation and flap coverage (free fascial anterolateral thigh flap) in a single sitting. Patients were contacted at a minimum of 30 months to measure HRQoL. Intervention: Patients requiring ORDB versus those who did not require the use of devitalized bone as part of their orthoplastic reconstruction. Main Outcome Measurements: The primary outcome measure was HRQoL ascertained using Euro-Qol (EQ)-5D and Short-Form (SF)-36 scores. Results: Thirty (n = 30) patients underwent ORDB with the remaining 44 not requiring devitalized bone as part of their reconstruction. The median age was 46.5 years [interquartile range (IQR) 29.0], with a median follow-up of 3.8 years (IQR 1.5). The median cohort EQ-5D was 0.743 (IQR 0.222), ORDB 0.743 (IQR 0.195) versus non-ORDB 0.748 (IQR 0.285), P = 0.71. The median physical component SF-36 score was 80 (IQR 50), ORDB 80 (IQR 34.5) versus non-ORDB 77.5 (IQR 58.75), P = 0.72. The median mental component SF-36 score was 80 (IQR 28), ORDB 80 (IQR 21) versus non-ORDB 80 (IQR 36), P = 0.29. Conclusions: In patients who sustained a type IIIB open tibial shaft fracture and who underwent a 2-stage orthoplastic reconstruction, ORDB does not seem to be associated with inferior health-related quality of life based on EQ-5D or SF-36 scores. The results of this approach should be considered within the strict combined orthoplastic approach in the study unit. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.